Anxiety as a Mediator between Procrastination and Work Engagement for Administrators - Alluhaidan, Alhanoof Mansour; Alhussein, Ahmed Mohammed Ahmed (Journal of Educational and Psychological Sciences, 2025)
This study aimed to explore anxiety as a mediator between procrastination and work engagement among administrative employees. Employing a descriptive research design with both correlational and comparative aspects, the study included a sample of 417 male and female Saudi employees working in in the government, semi-government, and private sectors within the Kingdom of Saudi Arabia, selected through convenience sampling. The research used the Arabic Scale of Procrastination (ASP) by Abdulkhaliq and Al-Dughayyem (2011), Beck Anxiety Inventory (BAI) by Beck et al. (1988), the instrument was translated and standardized by the researcher, and Utrecht Work Engagement Scale (UWES) by Schaufeli and Bakker(2004). 1.statistically significant negative inverse relationship between procrastination and work engagement among administrative employees. 2. There is a weak relationship between procrastination and work engagement when accounting for the impact of anxiety.  3. procrastination exhibited a greater predictive contribution to work engagement compared to anxiety. Both procrastination and anxiety negatively predicted work engagement, indicating that an increase in both procrastination and anxiety predicted lower work engagement, while a decrease in both predicted higher work engagement.  4. The study found no statistically significant differences in procrastination based on gender and sector variables among administrative employees. 5. significant differences in anxiety were observed based on gender, favoring female employees, while no significant differences were noted based on sector among administrative wmployees. 6. The study found no statistically significant differences in work engagement based on gender and sector variables among administrative employees. In light of the results of the study, the researcher presented a number of recommendations supporting work engagement and reducing procrastination and anxiety, which were directed to various professional organizations and institutions.
Keywords: anxiety; procrastination; job engagement; administrative employees